PENGEMBANGAN SISTEM CUSTOMER RELATIONSHIP MANAGEMENT BERBASIS WEB PADA PT. TERUS MEGA TARA JAKARTA - Erikson Damanik; Ivana Maretha Siregar (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2021)
This study aims to develop a web-based CRM (Customer Relationship Management) system at the company PT. Terus Mega Tara authorized agent of AIWA electronic products. To improve service to customers and establish relationships with customers which have been done manually, it is necessary to build a web-based CRM media that can make it easier for customers to obtain the information services needed without the need to spend a lot of time and money visiting the company concerned This web-based CRM system can increase customer loyalty, provide customer satisfaction and increase the company's business opportunities in facing increasingly advanced business competition. With the existence of a web-based Customer Relationship Management (CRM) system at PT. Terus Mega Tara enables companies to improve services to their customers.